Innate and Adaptive Immunity in the Tumor Microenvironment - Yefenof, Eitan; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Cancer cells are continuously interacting with the immune system of the host. These interactions can be regarded as a double edged sword. On the one hand, innate and adaptive immune responses act to protect the host by attempting rejection of the tumor. On the other hand, inflammatory cells and proteins stimulate multiplication and dissemination of cancer cells, thereby accelerating the progression of the disease. Traditionally, the interplay between cancer cells and host immunity has been studied systemically, with no particular attention to the site at which a given tumor develops. Recent studies, however, indicate that the tumor microenvironment is unique in providing both supportive and inhibitory factors that determine the fate of the tumor and its host. Accordingly, microenvironmental immunity that operates inside and around a tumor plays a crucial role in cancer development and progression. The aim of the present volume is to compile reviews on innate and adaptive immune responses at the tumor microenvironment with emphasis on positive and negative outcomes that affect the progression of the disease. These reviews have been solicited from experts in the field who published original research studies focusing on these issues.
Immune Effector Cells in the Tumor Microenvironment: Their Role in Regulation of Tumor Progression -- Histocompatibility Antigens, Tumor Microenvironment and Escape Mechanisms Utilized by Tumor Cells -- Local Tumor Growth and Spontaneous Systemic T Cell Responses in Cancer Patients: A Paradox and Puzzle -- Insights into Mechanisms of Immune Resistance in the Tumor Microenvironment through Molecular Profiling -- Tumor Antigens as Modulators of the Tumor Microenvironment -- Tumor Cell Resistance to Apoptosis by Infi ltrating Cytotoxic Lymphocytes -- The Tumor Microenvironment as a Model for Tissue-Specific Rejection -- Functional Cytotoxicity of T Cells in the Tumor Microenvironment -- Natural Killer Cells at the Tumors Microenvironment -- Contribution of the Microenvironment to the Pathogenesis of EBV-Positive Hodgkin and Nasal NK/T-cell Lymphomas.
Keywords: Medicine; Cancer research; Immunology; Oncology; Cell biology; Biomedicine; Cancer Research; Oncology; Immunology; Cell Biology; Biomedicine general; Electronic books